DIFFERENT PACKAGING METHODS EFFECTS ON SENSORY QUALITY AND CHEMICAL CRITERIA OF MARINATED SHAD (ALOSA IMMACULATA, B., 1838) - M.E. Erdem; S. Koral; S. Isidan (Chiriotti Editori, 2015)
In this study the sensory and chemical parameters of marinated shad (Alosa immaculata, Bennett, 1838) were determined. Fish were marinated with different package methods (in brine, oil and vacuum packed) and stored at 4±1°C. During the storage period, diffusion of proximate composition, acetic acid and sodium chloride into the fish fillets were determined. At the end of 7 months storage period, TVB-N were 8.05, 16.81 and 17.56 (mg/100 g), TMA were 2.28, 2.53 and 2.73 (mg/100 g), TBA were 7.08, 7.13 and 6.05 (mg malonaldehyde/kg) and pH were 4.42, 4.72 and 4.77 for brine, oil and vacuum packed samples, respectively. Throughout the storage period, effect of different package methods on TVB-N, TMA, TBA, pH, aw, acetic acid, sodium chloride and sensory issues were significant (p<0.05).